Learning and Consolidation of Declarative Memory in Good and Poor Readers of English as a Second Language - Sengottuvel, Kuppuraj; Vasudevamurthy, Arpitha; Ullman, Michael T.; Earle, F. Sayako (Frontiers in Psychology, 2020)
Declarative memory abilities may be important for children who are learning to read in a second language. In the present study, we investigated declarative memory in a recognition memory task in 7-to-13-year-old, Kannada native-speaking, good (n = 22) and poor (n = 22) readers of English, in Karnataka, India. Recognition memory was tested shortly (~10 minutes) after encoding (day 1) and again on the next (day 2). Analyses revealed that the two groups did not differ in recognition memory performance on day 1. On day 2, the good readers improved from day 1, whereas poor readers did not. A partial correlation analysis suggests that consolidation – the change in performance in recognition memory between the two days – is associated with reading skills in good readers, but not in poor readers. Taken together, these results suggest that children who struggle to read in a second language may have deficits in declarative memory consolidation.